Textual Analysis in TEDxSalem Speech on 'Prioritizing mental health in schools by Hailey Hardcastle': English - Nadia Fadzila (Warmadewa University, 2022)
This study aims to determine the realization of textual metafunctions and the types of themes that are dominated in speeches about mental health on the TEDxSalem YouTube channel entitled 'Why you should take a break: Prioritizing mental health in schools and brought by Hailey Hardcastle. The method in this research is qualitative with a content analysis approach. The data was obtained from the speech text and the data were analyzed using Halliday's Theory by considering the data analysis steps proposed by Gay et al. From the results of the analysis, it was found that the realization of the textual metafunction in Hailey Hardcastle's speech was applied. Found 105 clauses in the speech. And in those 105 clauses, there are themes and rhymes that mediate messages to their listeners. So it can be concluded that based on the textual metafunction perspective, the speaker tries to attract the listener's attention to focus more on the message of what is being said, and gives a lot of statements to tell the listener his confession that mental health should be considered the same as physical health and preferably starting at an early age.